Extra-linguistic factors of Ukrainian terminology fund development - Боярова, Людмила Георгіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The article analyzes the effects on Ukrainian terminology fund development, produced by the complex of extra-linguistic factors of socio-linguistic nature. The complex covers social and political processes in Ukraine, language policy and language planning in terminology. These factors are correlated with each other; social and political processes establishing the language policy of the government, the language policy determining the goal of language planning in the terminology and stating the normalization criteria for special-purpose language units. The correlation between the lingual and social phenomena has been considered within the tree stages of the period from the 20-s of the XXth century till nowadays, taking into account different language policies in Ukraine in each of these stages, resulted by social and political events.